ANALISIS KINERJA TENAGA KEPENDIDIKAN DALAM LAYANAN PENDIDIKAN - Mujahid, Tamimi; Darmansah, Tengku; Azzhara, Aliyyah Putri; Ramadina, Rifda; Habibah, Alfi Hafifah (Yayasan Amanah Nur Aman, 2024)
This study analyzes the performance of administrative staff in delivering educational services in schools. The research focuses on the role of administrative staff in educational administration, covering information services, infrastructure, staffing, and student welfare. Using a qualitative method, the study identifies various challenges faced by the administrative team, including a lack of speed and responsiveness in service delivery. The findings indicate that overall performance is satisfactory but requires improvements in efficiency and service responsiveness. Recommendations include additional training for administrative staff to enhance their competence in effectively and efficiently meeting school administrative needs.